Effect of Ankle Strategy Exercise on Balance Improvement and Fall Risk Reduction in the Elderly - James WH Manik; Citra Puspa Juwita; Tumbur Boy (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Older adults face a heightened risk of falling both indoors and outdoors due to age-related declines in balance. One contributing factor is weakness or instability in the ankle joint, which can significantly impair postural control and lead to limitations in daily activities. As balance deteriorates, functional capacity in the lower limbs declines, further hindering mobility and independence. Enhancing ankle strength and stability is therefore essential to improving balance and reducing fall risk in this population. This study investigates the impact of Strategic Ankle Exercise on balance and falling risk among older adults. Employing a one-group pre-test and post-test experimental design, the study involved 33 participants who met the inclusion criteria and were selected through total sampling. Balance was assessed using the Berg Balance Scale (BBS) and the Timed Up and Go (TUG) test. Paired sample t-tests conducted via SPSS revealed a significant improvement in dynamic balance following the intervention: BBS scores increased from 44 to 50.8, while TUG scores decreased from 15.5 to 10.1 (p < 0.001). A correlation analysis indicated a strong negative relationship between changes in BBS and TUG scores (r = -0.86; p < 0.001), suggesting that improvements in balance were associated with reduced fall risk Strategic Ankle Exercise emerges as an effective, evidence-based intervention for enhancing balance and minimizing fall risk in older adults. These findings support the integration of this program into geriatric care strategies. Future research should explore optimal exercise dosage and customization to maximize benefits across diverse age groups and functional levels. Keyword: Balance, Ankle strategic exercise, BBS, TUG